USING ENGLISH MOVIE TO ENHANCE STUDENTS INTEREST IN SPEAKING SKILL AT SMAN 1 GALIS PAMEKASAN - Fujiono; Zumam, Wildona (English Education:Journal of English Teaching and Research, 2020)
English movie is one of the media for teaching Learning process, it can make the students interest and also evoke the imagination of the students, so that the students have the idea to explore about their mind and they will convey in English Language. This study is aimed at explaining the implementation of Using English movies to enhance speaking skills. The method of the research is Class Room action Research. The subject of the research was Tenth-grade SMAN 1 Galis Pamekasan Madura. The data collection techniques were observation, interview, pre-test and post-test. The research finding showed that problem- based learning strategy spent a good result of English movies in teaching-learning speaking skills in the English language. Based on the result of this study, it is recommended that English Movies as media to enhance speaking skills. Key Words : Enhance , speaking skill , English Movie